Digital diaspora : a race for cyberspace - Everett, Anna, 1954- (Albany, NY : SUNY Press, 2009)
Traces the rise of black participation in cyberspace, particularly during the early years of the Internet. The author challenges the problematic historical view of black people as quintessential information-age outsiders or poster children for the digital divide by uncovering their early technolust and repositioning them as eager technology adopters and consumers, and thus as co-constituent elements in the information technology revolution. Offers case studies that include lessons learned from early adoption of the Internet by the Association of Nigerians Living Abroad and their Niajanet virtual community, the grassroots organizing efforts that led to the Million Woman March, the migration of several historical black presses online, and an interventionist critique of race in contemporary video games.
Toward a theory of the egalitarian technosphere : how wide is the digital divide -- Digital women : the case of the million woman march online and on television -- New black public spheres : the case of the black press in the age of digital reproduction -- Serious play : playing with race in contemporary culture -- The revolution will be digitized : reimaging Africanity in cyberspace.
Includes bibliographical references (pages 223-236) and index.
Print version record.
English.
JSTOR
Keywords: Computers -- Social aspects -- United States; African Americans and mass media -- United States; Digital media -- Social aspects -- United States; African diaspora; Ordinateurs -- Aspect social -- États-Unis.; Noirs américains et médias -- États-Unis.; Médias numériques -- États-Unis -- Aspect social; Africains -- Pays étrangers.; COMPUTERS -- Social Aspects -- General; African Americans and mass media; African diaspora; Computers -- Social aspects; Digital media -- Social aspects; United States; Digitale Spaltung; Internet; Massenmedien; Schwarze; USA; Schwärze; Gesellschaft; Digitale Spaltung; Digitale Medien; Schwarze; USA; SOCIAL SCIENCE / Ethnic Studies / American / African American & Black Studies